Analysis of the Use and Application of Mathematics in Economics: Demand and Supply Functions - Lubis, Andrew Satria; Zulfan; Chania, Mutia Fitri; Adha, Ishbir Mujahid (Talenta Publisher, 2024)
The aim of this study is to analyze how mathematics is used in economics in terms of the function of supply and demand, which is an important concept in the economy that explains the relationship between the price of goods or services and the quantity requested or offered. Using a mathematical approach, these concepts can be described more quantitatively and accurately, allowing for a more in-depth analysis of the functions of demand and supply. To determine the components that influence changes in supply and demand, mathematical models such as linear regression and elasticity analysis are used. In addition, the study examines how price changes affect market balance and how the functioning of supply and demand can be influenced by things that come from outside, such as government policies and the global economic situation. Research results show that analysis of the function of supply and demand using mathematical models gives us a better understanding of market dynamics. For example, analysis of demand elasticity shows how sensitive consumers are to price changes, and analysis of supply shows how prepared producers are for price changes. Policymakers and market players can make more strategic and informational choices by knowing these mathematical relationships. The study found that mathematics improved the predictability and accuracy of economic analysis and provided essential tools for good decision-making in various economic contexts.